Study the Relationship Between Teacher Literacy and Student Learning Outcomes in Math - Yingzi Wu; Nur Fauziyah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
The rapid development of science and technology significantly improved the quality and efficiency of education. This paper aimed to study mathematics, the most important subject in high school education, and explored how teachers' technological literacy, curriculum design, attitudes towards technology, and professional development for technology integration affected the student learning outcomes in the form of a questionnaire about 214 teachers who participated. The objective consistency index (IOC) was used to evaluate the content validity of the project during the research phase. The results showed that, except for one item, all other items exhibited good consistency. From most to least significant, the factors influencing student learning outcomes are teachers' technical literacy > curriculum design > attitude toward technology > development of mathematics education for teachers, with correlation coefficients of 0.608, 0.447, 0.436, and 0.289, respectively. Teacher technological literacy, curriculum design, and attitude toward technology were significantly positively correlated with student learning outcomes and could promote learning effectiveness. Technology was developing rapidly. Teachers' technical literacy, curriculum design, and attitude towards technology were all actively changed with the times, effectively stimulating students' interest in learning from multiple dimensions and thus improving students' confidence in learning.